Effect of Functionalized MWCNTs on Mechanical Properties of Polymer Matrices - Her, S.C.; Lai, C.Y. (Asian Journal of Chemistry, 2014)
The effect of functionalization of multi-walled carbon nanotubes (MWCNT) on the mechanical properties of MWCNT/epoxy nanocomposites was investigated. Epoxy-based nanocomposites reinforced with MWCNTs with and without functionalization were prepared. The properties of nanocomposites were characterized using scanning emission microscopy (SEM) and tensile test. Experimental results showed that the functionalization of MWCNTs improved the dispersion of MWCNTs in epoxy matrix along with enhanced mechanical properties compared to those containing MWCNTs without functionalization. Compared to the neat epoxy, nanocomposites prepared with 1 wt % of MWCNT-COOH exhibited 39 % increase in Young’s modulus and 19 % increase in tensile strength.